INTEGRATING ANIME FANDOM ENGAGEMENT, SOCIAL INFLUENCE, AND BRAND EXPERIENCE WITHIN THE THEORY OF PLANNED BEHAVIOR FRAMEWORK: A STUDY ON GENERATION Z’s REPURCHASE INTENTION TOWARD UNIQLO COLLABORATIVE FASHION IN JAKARTA - Lailly Rahmadini; Adilla Anggraeni (Sampoerna University, 2026)
The growing consumption of Japanese popular-culture-based fashion among Generation Z reflects a shift from utilitarian purchasing toward identity expression and emotional engagement, yet research integrating fandom engagement, social influence, and brand experience within a single framework to explain repurchase intention remains limited. This study examines how these three antecedents shape Generation Z’s repurchase intention toward Uniqlo UT’s anime-themed collaborative fashion products in Jakarta through the lens of the Theory of Planned Behavior (TPB). A quantitative explanatory design was applied using a cross-sectional survey of 228 Generation Z respondents (aged 17-28) domiciled in Jakarta who had previously purchased Uniqlo UT anime-themed products, selected through purposive sampling and analyzed with Partial Least Squares Structural Equation Modeling (SmartPLS 4.0). All six hypothesized paths were empirically supported: fandom engagement, social influence, and brand experience positively influenced attitude toward behavior, subjective norm, and perceived behavioral control respectively, which in turn fully mediated the effects of these antecedents on repurchase intention through a serial structural pathway. Brand experience, channeled through perceived behavioral control, emerged as the model’s dominant pathway, indicating that while fandom affiliation draws consumers to an initial purchase, it is consistent product quality, sizing reliability, and purchase accessibility that most strongly determine whether they return for subsequent collaborative releases. These findings extend TPB into popular-culture-based consumption and offer practical implications for fashion brands designing collaboration strategies grounded in brand experience and fandom community engagement.